Topalang Ges Unitary Enterprise - Abduraxmonov Aziz Mahmud o’g’li; Do’stmurodov Jahongir (Zien Journals, 2022)
The theme of the project "My idea": Modern methods of road lightingOur project focuses on the use of wind and solar energy in the social and service spheres of life
Keywords: phototrophic cyanoprocaryotes; blue-green algae; genome; colony